Omega-3 polyunsaturated fatty acids augment the muscle protein anabolic response to hyperinsulinaemia-hyperaminoacidaemia in healthy young and middle-aged men and women - Smith, Gordon I; Atherton, Philip; Reeds, Dominic N; Mohammed, B Selma; Rankin, Debbie; Rennie, Michael J; Mittendorfer, Bettina (Clinical science (1979), 2011)
Increased dietary LCn-3PUFA (long-chain n-3 polyunsaturated fatty acid) intake stimulates muscle protein anabolism in individuals who experience muscle loss due to aging or cancer cachexia. However, it is not known whether LCn-3PUFAs elicit similar anabolic effects in healthy individuals. To answer this question, we evaluated the effect of 8 weeks of LCn-3PUFA supplementation (4 g of Lovaza®/day) in nine 25-45-year-old healthy subjects on the rate of muscle protein synthesis (by using stable isotope-labelled tracer techniques) and the activation (phosphorylation) of elements of the mTOR (mammalian target of rapamycin)/p70S6K (p70 S6 kinase) signalling pathway during basal post-absorptive conditions and during a hyperinsulinaemic-hyperaminoacidaemic clamp. We also measured the concentrations of protein, RNA and DNA in muscle to obtain indices of the protein synthetic capacity, translational efficiency and cell size. Neither the basal muscle protein fractional synthesis rate nor basal signalling element phosphorylation changed in response to LCn-3PUFA supplementation, but the anabolic response to insulin and amino acid infusion was greater after LCn-3PUFA [i.e. the muscle protein fractional synthesis rate during insulin and amino acid infusion increased from 0.062±0.004 to 0.083±0.007%/h and the phospho-mTOR (Ser2448) and phospho-p70S6K (Thr389) levels increased by ∼50%; all P<0.05]. In addition, the muscle protein concentration and the protein/DNA ratio (i.e. muscle cell size) were both greater (P<0.05) after LCn-3PUFA supplementation. We conclude that LCn-3PUFAs have anabolic properties in healthy young and middle-aged adults.